Growing the Taraco Peninsula: Indigenous agricultural landscapes - Bruno, Maria C., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2024)
Examines the early history of farming (1500 BCE to 1150 CE) on the Taraco Peninsula, Bolivia drawing upon ethnographic insights from modern-day Indigenous farming practices and archaeological evidence to explore the landscapes and human-plant relationships that were shaped by Indigenous communities and their agricultural practices.--Provided by publisher.
Indigenous agriculture and resurgent communities: defining Taraco Peninsula landscapes -- Taraco Peninsula communities: space, place, and time -- Field preparation: earth, water, and variability -- Planting: growing domesticated plants -- Tending: wild plants and domesticated animals -- Harvesting and processing: transforming plants into food (Part 1) -- Eating: transforming plants for food (Part 2) -- Agricultural taskscapes: resurgent communities of the Taraco Peninsula.
Keywords: Taraco (La Paz, Bolivia: Municipio) -- Antiquities; Agriculture -- Bolivia -- Taraco (Municipio) -- History; Indians of South America -- Agriculture -- Bolivia -- Taraco (Municipio) -- History; Traditional farming -- Bolivia -- Taraco (Municipio) -- History; Plant remains (Archaeology) -- Bolivia -- Taraco (Municipio); Environmental archaeology -- Bolivia -- Taraco (Municipio); Botany -- Research -- Bolivia -- Taraco (Municipio); Sustainable agriculture -- Bolivia -- Taraco (Municipio)